Public Relations 2.0 na przykładzie analizy profili bibliotek uniwersyteckich na portalu społecznościowym Facebook - Bikowska, Katarzyna (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
The communications revolution implemented by social media has also influenced on public relations in libraries. Academic libraries, identified mainly with information and scientific activity, considered some new communications requirements of a user and the intercourses with environment via Facebook social network. How did the choice of communications tools 2.0 influence the relations with environment and the image of discussed libraries? In order to obtain an answer, the author of the article analysed tools and contents used by university libraries profiles on Facebook. The analysis was supplemented with the description of the interview’s results, conducted with administrators of university libraries’ profiles on Facebook.